EKSPLORASI CO-CREATION EXPERIENCE DALAM PENGEMBANGAN NILAI TAMBAH PRODUK WISATA KREATIF: STUDI KASUS DESA WISATA KANDRI, JAWA TENGAH - Mohammad Aqshal; Nina Mistriani (JURNAL ILMIAH EDUNOMIKA, 2024)
ABSTRACT This study aims to explore how co-creation experience plays a role in developing added value for creative tourism products in Kandri Tourism Village, Central Java. Using a qualitative approach, this case study delves into the perceptions and experiences of local stakeholders and tourists in the co-creation process of tourism products. Data collection methods include in-depth interviews, participatory observation, and focus group discussions with creative business actors, tourism village managers, and tourists. Data analysis was conducted through thematic coding and narrative interpretation. The results show that co-creation experience facilitates more authentic and high-value product innovation, increases local community involvement in tourism development, and strengthens emotional bonds between tourists and the destination. Significant impacts are seen in the increased competitiveness of local creative tourism products and the economic empowerment of village communities. This study contributes to a deeper understanding of co-creation dynamics in the context of rural tourism based on the creative economy. Keywords: co-creation experience; tourism products; creative economy; tourism village. ABSTRAK Penelitian ini bertujuan untuk mengeksplorasi bagaimana co-creation experience berperan dalam pengembangan nilai tambah produk wisata kreatif di Desa Wisata Kandri, Jawa Tengah. Dengan menggunakan pendekatan kualitatif, studi kasus ini menggali persepsi dan pengalaman stakeholder lokal serta wisatawan dalam proses ko-kreasi produk wisata. Metode pengumpulan data meliputi wawancara mendalam, observasi partisipatif, dan focus group discussion dengan pelaku usaha kreatif, pengelola desa wisata, dan wisatawan. Analisis data dilakukan melalui coding tematik dan interpretasi naratif. Hasil penelitian menunjukkan bahwa co-creation experience memfasilitasi inovasi produk yang lebih autentik dan bernilai tinggi, meningkatkan keterlibatan komunitas lokal dalam pengembangan wisata, serta memperkuat ikatan emosional antara wisatawan dan destinasi. Dampak signifikan terlihat pada peningkatan daya saing produk wisata kreatif lokal dan pemberdayaan ekonomi masyarakat desa. Studi ini berkontribusi pada pemahaman yang lebih mendalam tentang dinamika co-creation dalam konteks pariwisata pedesaan berbasis ekonomi kreatif. Kata Kunci: co-creation experience; produk wisata; ekonomi kreatif; desa wisata.